HUBUNGAN PAPARAN ROKOK, KONSUMSI TEH, JARAK KELAHIRAN DENGAN ANEMIA IBU HAMIL DI BPM KERTAPATI - Sundari, M Sri; Minarti, Minarti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Functional anemia is defined as a decrease in the number of erythrocyte masses so that it cannot fulfill its function to carry sufficient amounts of oxygen to peripheral tissue. The prevalence of anemia in pregnant women in Asia is 48.2%, while for Southeast Asia itself it is 97.8%. Purpose : Of this study is to find out whether there is a relationship between exposure to cigarette smoke, frequency of tea consumption and distance of birth with anemia status in pregnant women in BPM Sundari Kertapati in 2019. Method : This research uses analytical survey research method with cross sectional research design. Sampling was done using random sampling obtained as many as 81 pregnant women. The instrument used was a questionnaire using the chi square test.Results : Showed that there was a significant relationship between exposure to cigarette smoke to anemia status with p = 0.007, there was no significant relationship between tea consumption and anemia status with p = 0.399, there was a significant relationship between birth distance against anemia status with p = 0.020. Suggestion : the role of health workers in providing counseling to pregnant women and husbands about the dangers of cigarette smoke and their effects on pregnancy is very necessary, as well as the frequency of tea that should not be consumed every day.Keywords: Anemia, Cigarette Smoke Exposure, Frequency of Tea Consumption and Birth Distance